2013
DOI: 10.1111/tid.12116
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter evaluation of pandemic influenza A/H1N1 in hematopoietic stem cell transplant recipients

Abstract: A(H1N1)pdm09 infection was particularly severe in HSCT recipients, specifically among those receiving augmented immunosuppression for graft-versus-host disease. The high mortality of the nosocomial cases highlights the need for strict infection-control measures in hospitals during influenza outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…However, no significant difference was observed by univariate analysis. Previous studies revealed GVHD and use of immunosuppressive agents as major risk factors associated with LRTI and mortality [46][47][48]. Because of the small number of patients who developed GVHD in our study, logistic regression analysis could not be performed.…”
Section: Discussionmentioning
confidence: 84%
“…However, no significant difference was observed by univariate analysis. Previous studies revealed GVHD and use of immunosuppressive agents as major risk factors associated with LRTI and mortality [46][47][48]. Because of the small number of patients who developed GVHD in our study, logistic regression analysis could not be performed.…”
Section: Discussionmentioning
confidence: 84%
“…PVS is a known phenomenon among stem cell transplant and adult SOT recipients, but it has rarely been investigated in LTRs . Gainer et al.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality rates of up to 25% have been reported in HCT patients with lower RTID (108). Retrospective comparative studies suggest more severe outcomes of the pandemic influenza A/H1N1/pdm09 than previous seasonal IV-A, with more patients suffering from lower RTID, hypoxemia, and mortality, where these outcomes were predicted by profound lymphopenia and delayed antiviral therapy (109,110). However, another large retrospective analysis of influenza A/H1N1/pdm09 diagnosed in 286 HCT patients (222 allogeneic, 64 autologous) at 18 months posttransplant reported cough, fever, and rhinorrhea in 85%, 81%, and 49%, respectively (30).…”
Section: Carv-specific Aspects In Transplant Patients Influenza Virusesmentioning
confidence: 99%